Synthesis and Physico-Chemical Characteristics of N-Methyl/Acetyl-3-phenyl semicarbazones - Mukesh,; Dr. Girja Shankar Tripathi, (International Journal of Scientific Research in Science and Technology, 2024)
This study presents the synthesis and comprehensive physico-chemical characterization of N-methyl/acetyl-3-phenyl semicarbazones. The semicarbazones were synthesized through a condensation reaction involving 3-phenyl hydrazine and various carbonyl compounds. The reaction conditions were optimized to achieve high yields and purity. The synthesized compounds were characterized using a range of techniques including NMR, IR, and mass spectrometry, confirming their molecular structures and functional groups. Thermal stability and melting points were determined through thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). Solubility and partition coefficient measurements were conducted to assess the lipophilicity of the semicarbazones. Furthermore, the electronic properties were evaluated using UV-Vis spectroscopy, while X-ray crystallography provided detailed insights into the crystal structures of selected compounds. The results highlight the influence of different substituents on the physico-chemical properties of the semicarbazones, contributing to their potential applications in pharmaceutical and material science fields. The study underscores the versatility of N-methyl/acetyl-3-phenyl semicarbazones as building blocks in organic synthesis and their relevance in the development of novel compounds with desired chemical and physical properties.
Keywords: UV-Vis Spectroscopy; Physico-Chemical Properties; Semicarbazones; 3-Phenyl Hydrazine; Carbonyl Compounds